Efficacy and Side Effects of Fractional Carbon Dioxide Laser for Acne Scars, Keloids, and Striae Albae in the Dermatovenereology Clinic of Tertiary Hospital: A Retrospective Study - Pramitha, Riezky Januar; Zulkarnain, Iskandar; Ervianti, Evy; Rahmadewi, Rahmadewi; Hidayati, Afif Nurul; Budiono, Budiono; Indramaya, Diah Mira; Setyaningrum, Trisniartami; Citrashanty, Irmadita; Sari, Maylita; Umborowati, Menul Ayu; Kusumaputra, Bagus Haryo; Listiawan, Muhammad Yulianto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Fractional Carbon Dioxide (CO2) LASER has better efficacy compared to conventional LASER in treating scar tissue such as acne scars, keloids, and striae albae. However, a population with darker skin has a higher risk of side effects, especially in post-inflammatory hyperpigmentation. Purpose: To evaluate the efficacy and side effects of fractional CO2 LASER in new patients with acne scars, keloids, and striae albae in the Dermatovenereology outpatient clinic. Methods: Retrospective analysis was done on 42 medical records of patients who met the inclusion criterion, which was those who have undergone fractional CO2 LASER treatments. The efficacy and side effects of the therapy were identified and analyzed using the Statistical Package for Social Sciences (SPSS) version 17 program. Result: A total of 42.9% of patients underwent fractional CO2 LASER treatments for acne scars, while 31% and 26.1% of patients received treatments for keloids and striae albae, respectively. There was a statistically significant decrease in the degree of acne scar (2.72 ± 0.83), keloid height (2.2 ± 0.405), and striae width (0.39 ± 0.02). The statistically significant side effects were hyperpigmentation (59.5%), crustae (26.2%), erythema â‰¥ for 4 days (19%), and new acne (19%). Conclusion: Fractional CO2 LASER was effective for treating scar tissue (acne scars, keloids, and striae albae) with a higher incidence of side effects in population with darker skin and post-inflammatory hyperpigmentation.